2019
DOI: 10.1155/2019/3486841
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 Exposure in the Respiratory System Induces Distinct Inflammatory Signaling in the Lung and the Liver of Mice

Abstract: Fine particulate matter 2.5 (PM2.5) is a harmful air pollutant currently threatening public health. Although many studies have been performed on the general negative effects of PM2.5 in mice and humans, the migration patterns of various immune cells in response to PM2.5 exposure remain unclear. In this study, we aimed to investigate the immune cell migratory response in the lung and the liver of intratracheally PM2.5-inoculated mice. To investigate the migration trajectory of immune cells in the lung and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Supporting the idea that lipolysis may be involved are studies showing that exposure to air pollution elevates catecholamines (48)(49)(50), which are potent activators of lipolysis enzymes (51) and could lead to the development of CAP-induced dyslipidemia. The potential involvement of the liver is supported by numerous studies showing that PM 2.5 promotes liver steatosis and fibrosis (52)(53)(54)(55). In addition, we found that biliverdin was elevated in mice exposed to the higher level of CAP, which may suggest some degree of liver damage.…”
Section: Discussionsupporting
confidence: 77%
“…Supporting the idea that lipolysis may be involved are studies showing that exposure to air pollution elevates catecholamines (48)(49)(50), which are potent activators of lipolysis enzymes (51) and could lead to the development of CAP-induced dyslipidemia. The potential involvement of the liver is supported by numerous studies showing that PM 2.5 promotes liver steatosis and fibrosis (52)(53)(54)(55). In addition, we found that biliverdin was elevated in mice exposed to the higher level of CAP, which may suggest some degree of liver damage.…”
Section: Discussionsupporting
confidence: 77%
“…We propose that keratinocytes and neutrophils could be the main sources of TNF-α after PM 2.5 exposure. Previous studies reported that PM 2.5 induces the recruitment of neutrophils ( 52 , 53 ), which produces TNF-α ( 54 ). Additionally, we demonstrated that FLG and LOR were inhibited by PM 2.5 , which did not affect IVL .…”
Section: Discussionmentioning
confidence: 99%
“…Doses of PM 2.5 were selected based on well accepted published literature. 1521 Group 3: mice were fed with chow containing TM5614 (10 mg/kg) for 6 days and then received PBS (25 μl X2 control) and TM5614 chow. Group 4: mice were fed with chow containing TM5614 (10 mg/kg) for 6 days and then received PM 2.5 (50-200 μg/mouse in 50 μl PBS; 25 μl X2) and TM5614 chow.…”
Section: Methodsmentioning
confidence: 99%